A Novel Candidate Gene for Temperature-Dependent Sex Determination in the Common Snapping Turtle. Issue 1 (1st May 2016) - Schroeder, Anthony L; Metzger, Kelsey J; Miller, Alexandra; Rhen, Turk
Abstract: Temperature-dependent sex determination (TSD) was described nearly 50 years ago. Researchers have since identified many genes that display differential expression at male- vs. female-producing temperatures. Yet, it is unclear whether these genes (1) are involved in sex determination per se, (2) are downstream effectors involved in differentiation of ovaries and testes, or (3) are thermo-sensitive but unrelated to gonad development. Here we present multiple lines of evidence linking CIRBP to sex determination in the snapping turtle, Chelydra serpentina . We demonstrate significant associations between a single nucleotide polymorphism (SNP) (c63A > C) in CIRBP, transcript levels in embryonic gonads during specification of gonad fate, and sex in hatchlings from a thermal regime that produces mixed sex ratios. The A allele was induced in embryos exposed to a female-producing temperature, while expression of the C allele did not differ between female- and male-producing temperatures. In accord with this pattern of temperature-dependent, allele-specific expression, AA homozygotes were more likely to develop ovaries than AC heterozygotes, which, in turn, were more likely to develop ovaries than CC homozygotes. Multiple regression using SNPs in CIRBP and adjacent loci suggests that c63A > C may be the causal variant or closely linked to it. Differences in CIRBP allele frequencies among turtles from northern Minnesota, southern Minnesota, and Texas reflect small and large-scale latitudinal differences in TSD pattern. Finally, analysis of CIRBP protein localization reveals that CIRBP is in a position to mediate temperature effects on the developing gonads. Together, these studies strongly suggest that CIRBP is involved in determining the fate of the bipotential gonad.